Caracterização e identificação de vírus em allium spp - Bampi, Daiana [UNESP] (2015)
The genus Allium includes important species used for human consumption, as garlic,onion and many other species grown as ornamentals. Some of these species are propagated vegetatively and can be infected by viruses belonging to the genera Allexivirus, Carlavirus and Potyvirus, often in mixed infections. Leek yellow stripe virus (LYSV) belongs to the genus Potyvirus and is considered the most important virus in Allium species. The complete genomic sequence of Leek yellow stripe virus garlic isolate from Brazil (LYSV-MG) has been determined. The LYSV-MG genome consists of 10,341 nucleotides and encodes a deduced polyprotein of 3,221 amino acids. Based on the analysis of the coding region for P1 protein, isolate LYSV-MG and others collected in garlic producing regions, could not be classified as belonging to the groups S and N. Brazilian isolates do not have the deletion present in the P1 from the S-type group but are more closely related to S-type than to N-type isolates. The Brazilian isolates formed a monophyletic group closer to S-type and one isolate from Okinawa, Japan. Brazilian isolates share 97-99% of P1 region nucleotide identity with each other, and 51-64% with different isolates from around the world. The data suggest that Brazilian LYSV isolates are derived from an ancestral source of the Okinawa and S-type isolates, prior to the P1 deletion and divergence in the S-type isolates. As part of the doctorate sandwich in United States Department of Agriculture, under the supervision of Dr. John Hammond, viruses present in ornamental Allium from Beltsville, MD were detected. Bulbs of fourteen different species of Allium were purchased from retail nurseries and planted in the field during the fall of 2013. Leaf tissue from the flowering symptomatic plants were collected during spring 2014, and tested by PCR using generic primers for the genus Allexivirus, Carlavirus and Potyvirus. PCR-positive ...